2007
DOI: 10.1080/09273940601174020
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy for Subfoveal and Juxtafoveal Choroidal Neovascularization Associated with Punctate Inner Choroidopathy

Abstract: vPDT is a beneficial resource in stabilizing and also improving VA in PIC patients affected with subfoveal and juxtafoveal CNV, although one third of the patients retain poor visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…The efficacy of intravitreal bevacizumab (Avastin; Genentech) for CNV secondary to PIC was suggested in a case report of a patient in Germany. 8 Photodynamic therapy as treatment for CNV in patients with PIC was evaluated in one study, 9 and while recurrences of CNV still occurred in nearly half of the patients after photodynamic therapy, every patient in this study showed cessation of leakage from their CNV on their final visit. Overall, the different treatment options that were used by our clinic in the management of recurrent CNV in patients with PIC had some evidence in the literature of improving the visual outcome.…”
Section: Discussionmentioning
confidence: 86%
“…The efficacy of intravitreal bevacizumab (Avastin; Genentech) for CNV secondary to PIC was suggested in a case report of a patient in Germany. 8 Photodynamic therapy as treatment for CNV in patients with PIC was evaluated in one study, 9 and while recurrences of CNV still occurred in nearly half of the patients after photodynamic therapy, every patient in this study showed cessation of leakage from their CNV on their final visit. Overall, the different treatment options that were used by our clinic in the management of recurrent CNV in patients with PIC had some evidence in the literature of improving the visual outcome.…”
Section: Discussionmentioning
confidence: 86%
“…[2][3][4][5] In specific, photodynamic therapy has been associated with the development of significant subfoveal atrophy, and the use of Argon laser photocoagulation is limited to the extrafoveal rather than the juxtafoveal and subfoveal CNVs because of the enlargement of scars after treatment and the subsequent treatment-induced visual loss. [2][3][4][5] Although according to the ANCHOR and MARINA studies, 6,7 intravitreal ranibizumab represents the accepted treatment for CNV on the background of AMD, the latter has not been standardized as the treatment of choice for CNV because of other causes. Recently, several reports 2,[8][9][10][11] suggested the off-label use of bevacizumab in inflammatory CNV with promising results.…”
Section: Discussionmentioning
confidence: 99%
“…1 The existing therapeutic modalities such as laser photocoagulation, photodynamic therapy, steroid administration, and surgical removal of the CNV are not always adequate and can be associated with a high rate of recurrence or potential complications. [2][3][4][5] Intravitreal ranibizumab, a fragment of a recombinant humanized monoclonal antibody Fab that has been approved by the Food and Drug Administration for intraocular use for the treatment of exudative AMD, according to the ANCHOR and MARINA studies, has been shown to be beneficial in repeated doses for CNV associated with this disease. 6,7 Based on the hypothesis of the pharmacologic inhibition of vascular endothelial growth factor playing a role in the therapeutic approach for inflammatory CNVs, bevacizumab (a monoclonal antibody that is formulated for intravenous infusion and is off-label for intraocular use) has been recently suggested by several authors.…”
mentioning
confidence: 99%
“…Retrospective and prospective case reports in verteporfintreated patients with CNV due to PIC have revealed improved VA in most cases (at least 63%) (Table 4) [74,75]. There have also been reports of improved or stabilized vision in most eyes (at least 70%) with choroiditis and [76][77][78][79][80][81][82].…”
Section: Verteporfin Pdt In Cnv Due To Inflammatory Conditionsmentioning
confidence: 99%